PSYCHOLOGICAL CHARACTERISTICS OF THE MANIFESTATION OF LIFE RESISTANCE DURING STUDENT AGE (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
The article is devoted to the issues of psychological aspects of the manifestation of tolerance to life during student life. First of all, an analysis of research conducted by foreign scientists on the content, characteristic aspects, criteria, indicators, and age-related development of the concept of resilience to life is presented. The results of an empirical study of the formation of resilience to life during student life are also presented.